2016
DOI: 10.1093/jac/dkw129
|View full text |Cite
|
Sign up to set email alerts
|

What prevents the intravenous to oral antibiotic switch? A qualitative study of hospital doctors' accounts of what influences their clinical practice

Abstract: The iv to oral switch interventions should tailor strategies to demystify iv versus oral antibiotic efficacy, engage consumers around the negative effects of iv antibiotic overuse and examine strategies to streamline team decision-making. Addressing these issues has the potential to reduce inappropriate antibiotic use and resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 28 publications
4
86
0
Order By: Relevance
“…It has been reported that there is often a failure in translating classroom knowledge into clinical prescribing practice, and there is discordance between knowledge and practice (Eyal and Cohen, 2006;Scaioli et al, 2015;Wasserman et al, 2017). More active educational approaches such as clinical case discussions and interactive elearning are generally considered to be more effective for influencing prescribing behaviours (Ohl and Luther, 2014;Broom et al, 2016;Wasserman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that there is often a failure in translating classroom knowledge into clinical prescribing practice, and there is discordance between knowledge and practice (Eyal and Cohen, 2006;Scaioli et al, 2015;Wasserman et al, 2017). More active educational approaches such as clinical case discussions and interactive elearning are generally considered to be more effective for influencing prescribing behaviours (Ohl and Luther, 2014;Broom et al, 2016;Wasserman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These concepts/strategies are utilized internationally (Shrahtey et al 2015;Broom et al, 2016;O'Donnell and Guarascio, 2017) and every veterinary undergraduate should be knowledgeable about them for obvious reasons: early switch from intravenous to oral AB reduces duration of AB therapy, length of hospital stay, intravenousassociated morbidity and improve cost effectiveness (Broom et al, 2016). De-escalation is a critical strategy in reducing resources (Minen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is needed to determine what proportion of patients receive IV antibiotics which could be administered orally. Prompt scheduled transfer to oral antibiotics when clinically indicated would reduce the need for PIVC and associated morbidity (Broom, Broom, Adams, & Plage, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, such use is more expensive to healthcare systems through higher antibiotic costs, increased length of hospital stay and increased nursing time 2. Although these risks are well described, a perception of greater potency and mythical qualities of intravenous antibiotics may prevent prompt intravenous to oral switching 3. Therefore, there is a need to balance the actual benefit of intravenous antibiotics against the known risks.…”
mentioning
confidence: 99%